2005
DOI: 10.1128/aem.71.8.4241-4247.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role for HtrA in Stress Induction and Virulence Potential in Listeria monocytogenes

Abstract: In silico analysis of the Listeria monocytogenes genome revealed lmo0292, a gene predicted to encode a HtrA-like serine protease. A stable insertion mutant was constructed, revealing a requirement for htrA in the listerial response to heat, acid, and penicillin stress. Transcriptional analysis revealed that htrA is not induced in response to heat shock but is induced in response to low pH and penicillin G stress. Furthermore, htrA expression was shown to be dependent upon the LisRK two-component sensor-kinase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 33 publications
5
78
0
Order By: Relevance
“…Interestingly, the genes encoding the LisRK two-component system were found to be induced 4.17-fold (lisR) and 3.93-fold (lisK), respectively (Supplementary Table S2). In addition, four genes previously shown to be affected by LisRK (htrA, lmo2210, lmo2229 and lmo2487) were highly upregulated in response to cefuroxime exposure (Supplementary Table S2) (Cotter et al, 2002;Gottschalk et al, 2008;Stack et al, 2005). Our transcriptional analysis also showed that the CesRK-regulated genes lmo0443, lmo1416, lmo2420 and lmo2812 were highly upregulated by cefuroxime exposure (Supplementary Table S2) (Gottschalk et al, 2008;Kallipolitis et al, 2003).…”
Section: Below)supporting
confidence: 50%
See 3 more Smart Citations
“…Interestingly, the genes encoding the LisRK two-component system were found to be induced 4.17-fold (lisR) and 3.93-fold (lisK), respectively (Supplementary Table S2). In addition, four genes previously shown to be affected by LisRK (htrA, lmo2210, lmo2229 and lmo2487) were highly upregulated in response to cefuroxime exposure (Supplementary Table S2) (Cotter et al, 2002;Gottschalk et al, 2008;Stack et al, 2005). Our transcriptional analysis also showed that the CesRK-regulated genes lmo0443, lmo1416, lmo2420 and lmo2812 were highly upregulated by cefuroxime exposure (Supplementary Table S2) (Gottschalk et al, 2008;Kallipolitis et al, 2003).…”
Section: Below)supporting
confidence: 50%
“…Thus, the cell envelope stress response of L. monocytogenes appears to be activated at multiple stages of the infectious process. In accordance with this, LisRK, CesRK and VirRS have been shown to contribute to pathogenesis in mice, and several of the genes shown to be highly upregulated in response to cefuroxime exposure play important roles in virulence, including dacA, lmo2714, htrA and the dlt-operon (Abachin et al, 2002;Camejo et al, 2009;Stack et al, 2005;Wilson et al, 2006;Woodward et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In L. monocytogenes, nine orthologues of these genes showed induction, including htrA. Other research has shown that HtrA is important for survival during exposure to environmental and cellular stresses (Stack et al, 2005;Wilson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%